Modern aproaches to diabetic macular edema diagnosticks - A. V. Doga; P. L. Volodin; E. V. Ivanova; D. A. Buryakov; O. I. Nikitin; F> A. Avakyan (Сахарный диабет, 2020)
Diabetic macular edema (DME) continues to be an important problem of modern ophthalmology and endocrinology. The risk of edema is higher in patients with type 2 diabetes. Thus, this is the main cause of irreversible vision loss in these patients. DME is one of the prognostically unfavorable and difficult to treat manifestations of diabetic retinopathy. As the main cause of vision loss in diabetic patients, diabetic macular edema is often not diagnosed immediately, which causes difficulties in the treatment of pathology. Thus, early diagnosis and timely treatment of this disease is the key to successfully counteract the uncontrolled decline in the patient’s visual functions. In this article, the team of authors highlighted the possibilities of informative instrumental research methods available in the Arsenal of modern ophthalmological services. Based on the analysis of modern literature, the main principles of these diagnostic methods were indicated, their key capabilities and limitations compared to each other were highlighted. Knowledge of these characteristics is, in our opinion, an integral and most important tool in the Arsenal of a practicing ophthalmologist who supervises patients with this pathology.